korelasi Korelasi Prestasi Belajar Produk Kreatif & Kewirausahaan dan Hasil Praktik Indrustri Dengan Minat berwirausaha Siswa SMK: Prestasi, Kewirausahaan, Praktik Indrustri, Minat Berwirausaha - Ahmad Suffendi (JURNAL VOKASI DEWANTARA (JVD), 2023)
The aims of this study are (1) to determine the correlation between Creative Product and Entrepreneurship Learning Achievement (PKK) with Entrepreneurial Interest. (2) To find out the correlation between Industrial Practice Results (PI) and Entrepreneurial Interest. (3) To find out the correlation between Creative Product and Entrepreneurship Learning Achievement (PKK) and Industrial Practice Results (PI) with Entrepreneurial Interest. This type of research is quantitative research, with a population of 65 students. The subjects taken consist of two classes, namely the TKR XIA class and the TKR XIB class at SMK Taruna Bangsa Pati. For data collection, the instrument used includes documentation and questionnaires. This data analysis technique uses a descriptive test, the analysis requirements test includes a normality test and a linearity test. This hypothesis test uses the Product moment correlation test and also the multiple correlation test. The results of this study (1) There is a positive and significant correlation between Creative Product Learning Achievement and entrepreneurship (PPK) with Entrepreneurial Interest. Judging from the results of the value of sig. (1-tailed) the result is 0.004 (positive) and rcount > rtable (0.616 > 0.224). (2) There is a positive and significant correlation between Industrial Practice Results (PI) and Entrepreneurial Interest. Judging from the results of the value of sig. (1-tailed) the result is 0.045 (positive) rcount > rtable (0.616 > 0.224). (3) There is a positive and significant correlation between Creative Product and Entrepreneurship Learning Achievement (PKK) and Industrial Practice Results (PI) with Entrepreneurial Interest. Judging from the results of the three test scores (0.616 > 0.224). Based on the results of this study, after going through the process using analyzes, it can be concluded that there is a correlation between Creative and Entrepreneurial Product Learning Achievements (PKK) and Industrial Practice Results (PI) with Entrepreneurial Interests in TKR XI class students at SMK Taruna Bangsa Pati with the results by 61.6%. It can be seen from the value of 38.4% obtained from other variables. So it is not included in the discussion in this study. It can be seen that the figure of 38.4% does not come from one variable but from making an effective contribution to students' self-interest, but this will also be divided into other variables. In this number there is the smallest achievement.